THE INFLUENCE OF MARKETING COMMUNICATION LIVE STREAMING ON TIKTOK ACCOUNT @SOMETHINCMAKEUP ON CONSUMER PURCHASING DECISION OF SOMETHINC MAKEUP PRODUCTS WITH BUYING INTEREST AS MEDIATOR VARIABLE - Putri Permata, Arrawinda; Sunarto, Sunarto; Bayu Widagdo, Muhammad (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The internet has become a business platform. In 2021, local brand Somethinc introduced its makeup products and carried out various promotions via TikTok social media. As a new entrant, Somethinc Makeup needs to increase its sales so that it can compete with other local brands. One of the marketing efforts they make is through live streaming on the TikTok application. This research aims to determine the influence of marketing communications via live streaming on TikTok on consumer purchasing decisions, with purchase interest as a mediator. This research uses the Elaboration Likelihood Model with non-probability sampling techniques. The sample consisted of 100 individuals aged 18-24 years who were TikTok users and followers of the @somethincmakeup account, had an interest in cosmetics, had purchased Somethinc cosmetic products, and had experience using Somethinc products. This consideration is based on the majority of TikTok users which are teenagers aged 18 - 24 years, and Somethinc's market segmentation demographic, namely women aged 15 and older. Hypothesis testing is carried out using Simple Linear Regression and Multiple Linear Regression by SPSS. Based on the research results, it was found; (1) first hypothesis: there is a positive and significant influence of marketing communications via live streaming on TikTok (X) on Purchase Decisions (Y) with a significant value of 0.000. (2) second hypothesis: the live streaming marketing communication variable on TikTok (X) has a positive and significant effect on Purchase Interest (M) with a significant value of 0.000, so that the better the marketing communication activities via live streaming on TikTok (X), the higher the purchase interest. (3) the third hypothesis is accepted where there is a positive and significant influence between marketing communications via live streaming on TikTok (X) on purchasing decisions (Y) which is partially mediated by Purchase Interest (M) with a significant value of 0.00.